Características epidemiológicas-clínicas y tratamiento antibiótico inicial en niños con pielonefritis aguda en el Hospital Regional Docente de Trujillo - García Gil, Antonio André (2014)
Urinary tract infections (UTI) are frequent in children, their management is affected by the non-specificity of their manifestations and the uncertainty of the prognosis of UTI, with important sequelae such as renal scarring, hypertension and end-stage renal disease. OBJECTIVE: To determine the epidemiological-clinical characteristics and the initial antibiotic treatment of children with acute pyelonephritis (PNA) treated at the Regional Teaching Hospital of Trujillo from 2002 to 2013. METHOD: 76 children aged 3 months to less than 15 years with a diagnosis of ANP were identified. RESULTS: Frequency of cases of ANP in hospitalized children: 1.36%. Women (76.32%) and men (23.68%). Age group: from 3 months to <2 years (65.79%) and from 2 to <15 years (34.21%). Irrigation factors: previous use of antibiotics (32.9%), previous UTI (17.1%), constipation (13.2%). Clinical manifestations: fever (92.1%), irritability (60.5%), poor general condition (50%), vomiting (47.4%), dehydration (35.5%), diarrhea (27.6%), cloudy urine (25%), PPL + ( 22.4%), diffuse abdominal pain and low urinary symptoms (21.1%). Main etiological agent: E. coli (89.5%). Initial antibiotic treatment: monotherapy (88.2%), intravenous administration (97.3%) and oral administration (2.7%); Ceftriaxone (56.7%), Amikacin (34.3%). CONCLUSION: A frequency of 1.36 / 100 cases of PNA was found for hospitalized children. It was more frequent in female infants. One third received antibiotics prior to diagnosis. Clinical manifestations vary according to sex and age group. Antibiotics were administered as intravenous monotherapy, with Ceftriaxone and Amikacin more frequently